2008
DOI: 10.1002/jssc.200800102
|View full text |Cite
|
Sign up to set email alerts
|

Descriptive structure–separation relationship studies in chiral ligand‐exchange chromatography

Abstract: A new approach to model and interpret the separation of amino acid enantiomers is described. The descriptive structure-separation relationship (DSSR) study of a set of amino acid enantiomer couples analyzed with two chiral selectors S-benzyl-(R)-cysteine ((R)-SBC) and S-trityl-(R)-cysteine ((R)-STC) has been performed with the aim to highlight the molecular properties of the analyte affecting the enantiodiscrimination process. Although with some exceptions, the classification models obtained with (R)-STC indic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 25 publications
0
21
0
Order By: Relevance
“…Davankov [36] reported that there is no thermodynamic without kinetic enantioselectivity, whereas the opposite assertion is not valid. With all the employed sulphur-containing chiral selectors and with the exception of His and AIDA, (S)-enantiomers are more retained than their antipodes [16,37]. Thiophene-derived amino acids do not represent exceptions since the presence of the sulphur atom reverses the usual amino acid priority.…”
Section: Comparison Among the Chromatographic Performances Obtained Fmentioning
confidence: 95%
See 2 more Smart Citations
“…Davankov [36] reported that there is no thermodynamic without kinetic enantioselectivity, whereas the opposite assertion is not valid. With all the employed sulphur-containing chiral selectors and with the exception of His and AIDA, (S)-enantiomers are more retained than their antipodes [16,37]. Thiophene-derived amino acids do not represent exceptions since the presence of the sulphur atom reverses the usual amino acid priority.…”
Section: Comparison Among the Chromatographic Performances Obtained Fmentioning
confidence: 95%
“…With all the adopted selectors, aspartic acid (Asp), F94C, O-phospho-serine (OPho-Ser) and ornitine (Orn) enantiomer couples did not experience any enantiorecognition. While a comparable enantioseparation of threonine (Thr) antipodes was achieved with (R)-STC and (R)-SDC, (R)-SBC was not effective thus providing for the enantiomers coelution [16]. With the exception of 5-MATIDA, F94B, cysteine (Cys) and CIP-B enantiomer couples which resulted better discriminated with (R)-SDC, a gain in enantiodiscrimination was obtained for all the remaining compounds when the most lipophilic chiral selector was engaged [(R)-STC].…”
Section: Comparison Among the Chromatographic Performances Obtained Fmentioning
confidence: 96%
See 1 more Smart Citation
“…separated or nonseparated racemates, can be easily individuated. This concept has been recently adapted by Natalini et al [148,149] that carried out a descriptive structure-separation relationship (DSSR) in which some set of physicochemical descriptors are directly used with a partition tree or a classification model towards the experimental enantioselectivities. In a quantitative form also Del Rio and Gasteiger [147] applied this idea to devise a simple method based on the atomic counts around the chiral centre to assess whether a compound will be separated or not on a Whelk-O1 CSP.…”
Section: Discussionmentioning
confidence: 99%
“…It is important not to confuse the discrete or continuous nature of the dependent variable with the building of quantitative or qualitative models. For instance, a classification problem can be both qualitative (see Natalini et al [148]) or quantitative (see Del Rio and Gasteiger [147]) as well.…”
Section: Discrete Versus Continuous Dependent Variablementioning
confidence: 99%